Effect of speed reading strategy for solving mathematics word problems in English on elementary school students’ learning outcomes and self-confidence - Rolina Amriyanti Ferita; Noormaliah Noormaliah (Math Didactic: Jurnal Pendidikan Matematika, 2021)
This descriptive quantitative study aims to determine the effect of speed-reading strategy for solving mathematics word problems in English on elementary school students’ learning outcomes and self-confidence. This research was conducted in the odd semester of 2020/2021 school year in one of the private elementary schools in Banjarbaru city, with 15 of grade 3rd students as the subject. The quantitative data obtained from pretes and posttest scores based on students’ responses were analyzed using SPSS 26 through the paired sample test of Wilcoxon because the data is not normally distributed. The results obtained indicated that the speed-reading strategy used did not significantly increase the students’ pretest to posttest scores due to the lack of repetition and the way of presenting learning materials that was less attractive to students. However, the speed-reading strategy may can increase students’ self-confidence so that they are more confident in answering the word problems without the help for translation although more research is needed.